Obstructive laryngeal polyps presenting with dyspnea: report of five rare cases - Zer Toros, Sema; Şahin Yılmaz, Aslı; Kılıç, Osman; Oysu, Çağatay (ENT Updates, 2015)
Generally vocal fold polyps are small lesions causing dysphonia. In rare occurrences they may be huge in size and may present with dyspnea, choking spells, wheezing and stridor. We present five cases with giant vocal fold polyps with hoarseness and severe respiratory problems. In this report, clinical presentation and management of large vocal fold polyps are discussed.